For a new critical edition of Alfieri's political treaties (Prassi Ecdotiche della Modernità Letteraria, 2018)
The contribution was proposed for the first time at the conference "Vittorio Alfieri: éditer, commenter, traduire" (Paris, 16-17 February 2018). The report from this conference is published in this issue of PEML: https://riviste.unimi.it/index.php/PEML/article/view/10451The paper shows the new critical edition (in preparation) of the two political-literary treatises by Vittorio Alfieri, Della Tirannide and Del Principe e delle Lettere. The attention is focused, in particular, on the Ferrero-Ventimiglia manuscript, unpublished witness of an intermediate draft carried out in Paris in 1789. The study contributes to the reconstruction of the history of the text trough the analysis of the relation between the manuscript and the first draft of 1777.
Keywords: Vittorio Alfieri; critical edition; author's philology; history of the text